Crustal deformation analysis in Zagros and Makran zones, based on GPS permanent network data - Sakhaei, Seyed Reza; Rostam, Ghasem Ghorbani (Contributions to Geophysics and Geodesy, 2020)
We present an analysis of strain based on the evaluation of crustal deformation in Zagros and Makran, which has implications in terms of the dynamics of the study area. We have used data from 17 permanent GPS stations of the Cartographic Centre of Iran spanning the period 2011–2013. The raw observed data were in RINEX format. The elements of strain tensor were calculated by a 2D isoparametric method and the inversion of strain equation. Then the dilatation (extension and compression) and shearing were obtained through the analysis of eigenvalue and eigenvector of tensors. In most cases compression has overcome the extension, which can be expected due to the convergence of the Arabia and Eurasia plates. The compression axis is nearly vertical along the Zagros causing reverse and thrust faults in Zagros. Due to the N–S trending of the Sabzvaran–Jiroft–Kahnuj fault system and to the direction of compression and extension, the system will be of strike–slip mechanism. Sudden changes of shearing can be used to identify the strike–slip faults. As observed in this study, there were sudden changes in shearing of the Rafsanjan and Jiroft–Kahnuj faults. The P/T axis rotates significantly in the Zagros–Makran transition zone. Moreover, the Makran's P/T axis is smaller than the P/T axis of Zagros, which demonstrates that the impact of the Arabian plate, moving towards Iran, is greater than the impact of the Indian subcontinent plate movement. The values of the counter-clockwise rotation rate at stations located east of the Zagros–Makran transition zone are higher than at other stations. Also the velocity vectors at stations were determined while using the software GAMIT/GLOBK.